Multiple positive solutions for quasilinear elliptic problems with sign-changing nonlinearities - Bonder, J.F. (2004)
Using variational arguments, we prove some nonexistence and multiplicity results for positive solutions of a system of p-Laplace equations of gradient form. Then we study a p-Laplace-type problem with nonlinear boundary conditions. Copyright © 2004 Hindawi Publishing Corporation.